Reactions of Plasmodium falciparum Ferredoxin:NADP(+) Oxidoreductase with Redox Cycling Xenobiotics: A Mechanistic Study - Lesanavičius, Mindaugas (Int J Mol Sci, 2020)
Ferredoxin:NADP(+) oxidoreductase from Plasmodium falciparum (PfFNR) catalyzes the NADPH-dependent reduction of ferredoxin (PfFd), which provides redox equivalents for the biosynthesis of isoprenoids and fatty acids in the apicoplast. Like other flavin-dependent electrontransferases, PfFNR is a potential source of free radicals of quinones and other redox cycling compounds. We report here a kinetic study of the reduction of quinones, nitroaromatic compounds and aromatic N-oxides by PfFNR. We show that all these groups of compounds are reduced in a single-electron pathway, their reactivity increasing with the increase in their single-electron reduction midpoint potential (E(1)(7)). The reactivity of nitroaromatics is lower than that of quinones and aromatic N-oxides, which is in line with the differences in their electron self-exchange rate constants. Quinone reduction proceeds via a ping-pong mechanism. During the reoxidation of reduced FAD by quinones, the oxidation of FADH(.) to FAD is the possible rate-limiting step. The calculated electron transfer distances in the reaction of PfFNR with various electron acceptors are similar to those of Anabaena FNR, thus demonstrating their similar “intrinsic” reactivity. Ferredoxin stimulated quinone- and nitro-reductase reactions of PfFNR, evidently providing an additional reduction pathway via reduced PfFd. Based on the available data, PfFNR and possibly PfFd may play a central role in the reductive activation of quinones, nitroaromatics and aromatic N-oxides in P. falciparum, contributing to their antiplasmodial action.